Pengaruh pupuk organik dan anorganik terhadap intensitas penyakit karat daun buncis (Phaseolus vulgaris L.) di kebun percobaan Manggoapi - Derek Kornelis Erari; Eko Agus Martatnto; Asti Loda Hamu Meha; Hangrie Jimmy Namserna; Yohanis Amos Mustamu (Fakultas Pertanian Universitas Papua, 2021)
The purpose of this study was to determine the application effect of some organic fertilizers and inorganic fertilizers on the intensity of bean leaf rust disease. This study was designed using a Randomized Block Design (RAK), repeated 3 times, with 10 treatments, namely control (P0), Papua Nutrient (P1), POC Agrica (P2), NPK 16:16:16 (P3), POC Nasa (P4), Green Tonic (P5), Liquid Chemical Fertilizer Solution (P6), Urea + KCL + Phosphate (P7), Organic Fertilizer MX Bio Bas BWI (P8), and SP – 36 (P9). The results showed that the application of Papua Nutrient fertilizer has a better effect in suppressing the development of the intensity of bean leaf rust disease. The resistance of all treatments to the bean leaf rust disease studied was classified as moderately resistant.